The anorexigenic effect of intra-mesopallium ghrelin is related to high plasma corticosterone levels in broiler chicks during the first week of life - Gastón, María Soledad (2021)
Ghrelin is peptide secreted primarily in the stomach that acts on the central nervous system to regulate energy metabolism and responses to stress. In chicken, it decreases feed intake, and it has been suggested that corticotropin-releasing hormone could mediate this response. The present study investigates whether intra-mesopallium ghrelin-induced anorexia could involve the activation of the hypothalamic pituitary adrenal axis in 4-6-day-old chickens. The results showed that ghrelin, administered in the intermediate mesopallium, decreased feed intake and increased plasma corticosterone levels. In addition, a significant negative relationship was observed between both responses, where higher concentrations of corticosterone were associated with lower food intake. However, no significant changes were observed in plasma levels of ACTH induced by intra-mesopallium ghrelin. Therefore, this adrenal activation could play a mediating role in the anorectic effect of central ghrelin in broilers. Furthermore, it cannot be ruled out that this area of the forebrain and the hypothalamic pituitary adrenal axis may constitute a brain network for the control of chicken feeding.